Relational Well-being Experiences of Previously Street Homeless Individuals in South Africa - Nel, San-Marié; Chigeza, Shingairai (International Journal on Homelessness, 2026)
There is a growing number of homeless individuals globally, and research increasingly recognises the importance of relationships and social support in promoting their well-being. However, limited attention has been given to the relational experiences of homeless individuals and the relationships that support their well-being during the transition out of homelessness. This qualitative study explored the relational well-being experiences of previously street homeless individuals residing in shelters in the City of Tshwane, South Africa. Data were collected through semi-structured, in-depth interviews with 12 participants and were analysed thematically. The findings show that the relational experiences and relationships of significance among previously homeless individuals are shaped by three interconnected drivers of relational well-being. First, previously street homeless individuals are relational subjects whose well-being is shaped by relationships with others and within their material and social contexts. Second, relationships function as a key means through which participants address material, emotional, and social needs. Third, personal experiences, societal conditions, and environmental contexts interact to either promote or undermine well-being during the transition out of homelessness. The study highlights the importance of relationally supportive shelter environments in facilitating sustainable transitions out of homelessness, with implications for policy, practice, and intervention design.